PENGEMBANGAN PERANGKAT PEMBELAJARAN SISTEM PERSAMAAN LINEAR DUA VARIABEL DENGAN MODEL PROBLEM BASED LEARNING - Lainata, Rosalinda Paulina; Damai, I Wayan; Pesik, Anekke (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2020)
Learning model that meets the criteria of being valid, practical and effective. This research is categorized as development research. This study uses the ADDIE model developed by Dick and Carey. There are five stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The learning tools produced in the study were the lesson plan (RPP), student activity sheets (LKPD) and evaluation of learning outcomes (EHB). The results showed that the products developed to meet the criteria of validity, practicality, and effectiveness. The learning device is feasible to use with an average score of the learning device assessment from the validate of 3.5 with valid criteria. The practicality of the learning device was seen from the student response questionnaire which gave a positive response and the teacher's ability to manage learning at the first meeting with an average of 3.69 and the second meeting of 3.46 which reached the good category, which was located in the interval 3.50 â‰¤ TKG < 4 , 50. The effectiveness of the learning device is seen from the test of student learning outcomes which shows the value of student learning completeness by an average of 80%.